PELATIHAN PERAN TIK DALAM TATA KELOLA MANAJEMEN ORGANISASI PADA LEMBAGA FILANTROPI DI KOTA PALEMBANG - Fahmi Ajismanto; Guntoro Barovih; febrianty Mustafa; Mutiara Lusiana Annisa; M. Abim Rifanda; Bagus Setiawan (LLPM Universitas Deli Sumatera, 2023)
A philanthropic institution is a trust or trust from the community to channel assistance from the community and for the community itself. In practice, there are still many philanthropic institutions, especially in Palembang, which still do not have knowledge of good organizational governance in terms of the utilization of information and communication technology. It can be seen that the management of data management is not yet well managed, so it requires an integration process of organizational management governance with information and communication technology in philanthropic institutions in the city of Palembang. Thus the purpose of community service is to increase understanding of organizational management governance with information and communication technology in the one Indonesian charity movement. In this service, one of the philanthropic institutions, namely One Amal Indonesia, will become a community service partner. The method used in this service is in the form of delivering material about the benefits of a management information system, special attention before implementing a management information system, management information systems that are often used in organizations, categories of management information systems (terms of cost), and high cost of ICT investment. After the presentation of the material, it was followed by a question and answer discussion between the institute's community service team.